Correlation between Students' Understanding of Islamic Legal Ethics and Anti-Corruption and Deradicalization Education - Nurhikmah; Al Ayyubi, Ibnu Imam; Prayetno, Eko; Apriyanti, Niken Siti Nur; Al-Ghatnaini, Raed Awadh Saeed (Journal of Education and Learning Sciences, 2024)
This study aims to analyze the correlation between students' understanding of Islamic legal ethics with anti-corruption and deradicalization education. Using a mixed methods approach with explanatory sequential design, this study combines quantitative analysis using the Spearman correlation test and qualitative analysis through interviews and observations. The results of the study indicate that there is no significant relationship between understanding of Islamic legal ethics with anti-corruption and deradicalization education, as indicated by a significance value of 0.827 (> 0.05) and a correlation coefficient of -0.032 which describes a very weak and negative relationship. This finding supports Alatas' opinion (2006) that understanding ethics and morals is not always directly proportional to real actions in fighting corruption and radicalism. Therefore, it is recommended that anti-corruption and deradicalization education prioritize an applicative approach based on experience and real case studies to increase its effectiveness. Therefore, educational institutions are expected to be able to design a more integrative and multidimensional curriculum to achieve more optimal results in anti-corruption and deradicalization learning.